Enhanced Synthesis of Volatile Compounds by UV-B Irradiation in Artemisia argyi Leaves - Haike Gu; Zhuangju Peng; Xiuwen Kuang; Li Hou; Xinyuan Peng; Meifang Song; Junfeng Liu (Metabolites, 2024)
Background: Volatile compounds have a deep influence on the quality and application of the medicinal herb Artemisia argyi; however, little is known about the effect of UV-B radiation on volatile metabolites. Methods: We herein investigated the effects of UV-B exposure on the volatile compounds and transcriptome of A. argyi to assess the potential for improving its quality and medicinal characteristics. Results: Out of 733 volatiles obtained, a total of 133 differentially expressed metabolites (DEMs) were identified by metabolome analysis. These were classified into 16 categories, primarily consisting of terpenoids, esters, heterocyclic compounds, alcohols, and ketones. Sensory odor analysis indicated that green was the odor with the highest number of annotations. Among the 544 differentially expressed genes (DEGs) identified by transcriptome analysis, most DEGs were linked to “metabolic pathways” and “biosynthesis of secondary metabolites”. Integrated analysis revealed that volatiles were mainly synthesized through the shikimate pathway and the MEP pathway. RNA-seq and qPCR results indicated that transcription factors HY5, bHLH25, bHLH18, bHLH148, MYB114, MYB12, and MYB111 were upregulated significantly after UV-B radiation, and were therefore considered key regulatory factors for volatiles synthesis under UV-B radiation. Conclusions: These findings not only provide new insights into UV-induced changes in volatile compounds, but also provide an exciting opportunity to enhance medicinal herbs’ value, facilitating the development of products with higher levels of essential oils, flavor, and bioactivity.